Fixing cobalt metal onto mordenite through spray impregnation and its evaluation as a catalyst in transforming used coconut cooking oil into bio-jet fuel - Saviola, Aldino Javier; Wijaya, Karna; Syoufian, Akhmad; Vebryana, Marini Fairuz; Anggraeni, Widuri; Rozana, Kharistya; Darsono, Nono; Saputra, Dita Adi; Saputri, Wahyu Dita (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
Given the challenges posed by fossil-based jet fuel, research into bio-jet fuel production has intensified to achieve carbon neutrality. The present work reports a significant breakthrough with the successful conversion of used coconut cooking oil into bio-jet fuel utilizing a cobalt-impregnated mordenite catalyst. Cobalt was introduced to mordenite via the spray impregnation method at a concentration of 2% using a CoCl?·6H?O solution. The resultant catalyst was characterized using FTIR, XRD, NH?-TPD, SAA, FESEM-EDX Mapping, TEM, XPS, and TG/DTA instruments. Hydrotreatment was conducted in a semi-batch reactor at atmospheric pressure, employing H? gas at a flow rate of 20 mL/min and a catalyst-to-feed ratio of 1:200 (w/w) for a duration of 2 h. The addition of cobalt significantly enhanced the efficiency of the hydrotreatment by improving the catalytic performance of mordenite as a support material. The liquid product conversion and total bio-jet fuel yield obtained from the hydrotreatment of used coconut cooking oil using the Co/mordenite catalyst were 60.25% and 51.11%, respectively. The highest selectivity for bio-jet fuel was observed in fraction II (450–550 °C) at 88.90%. This catalyst exhibited sustained performance over three consecutive runs, indicating its potential application in the future biofuel industry. Altogether, this research reveals the possibility of employing used coconut cooking oil as a sustainable and promising feedstock to be converted into bio-jet fuel by hydrodeoxygenation and/or hydrocracking reactions.